The girl's like spaghetti why, you can't manage without apostrophes! - Truss, Lynne; Timmons, Bonnie (New York G.P. Putnam's Sons, 2007)
See how using (or not using) an apostrophe can change the meaning of a sentence.
Keywords: English language -- Punctuation -- Juvenile literature; Apostrophe -- Juvenile literature; English language -- Punctuation; Apostrophe